MatLab-Simulink model of the digital data transmission with the use of chaotic masking - Vovchuk, Dmytro; Hahiuk, Serhii; Politanskii, Leonid; Ivanyshyn, Nazar (Видавництво Львівської політехніки, 2013)
The paper touches upon the topical problem of finding efficient ways to transmit hidden information and retrieve it. The use of a modified scheme of chaotic masking for messages bits of the hidden information is offered as an alternative. The information signal is a harmonic, chaotic or noise which initially modulates a digital signal, that’s why chaotic oscillations, generated by Chua’s circuit, proved to become a signal carrier. Some specific conditions for increasing signal secrecy in the channel with and without noise are investigated and reveals the possibility of information bits recovery with the help of MatLab-Simulink model.
Keywords: hidden information; chaotic masking; digital signal; chaotic and noise signal; scheme model